Factors associated with anxiety about handling contaminated patients during a nuclear disaster among disaster medical assistant teams in Japan: a cross-sectional study - Shibata, Hisami; Yamaguchi, Takumi; Yamada, Yumiko; Shinkawa, Tetsuko; Urata, Hideko; Matsunari, Yuko (Frontiers in Disaster and Emergency Medicine, 2024)
Introduction Japanese Disaster Medical Assistance Teams (DMATs) are pivotal in disaster response, especially during nuclear crises. The objective of this study was to identify factors associated with anxiety among Japanese DMAT personnel when handling contaminated patients during nuclear disasters. Materials and methods In this cross-sectional study, 609 Japanese DMAT members from Kyushu and Okinawa, Japan, were surveyed. Multivariate binomial logistic regression was used to determine anxiety predictors. Results Of the 276 respondents, 77.2% expressed anxiety about managing contaminated patients. Women and younger team members expressed the highest level of anxiety associated with handling contaminated patients during nuclear disasters. Conclusion This study revealed heightened anxiety among female and younger Japanese DMAT personnel regarding the handling of contaminated patients during nuclear disasters. Targeted training addressing these concerns is essential for effective disaster response.